The Profitability, Company Size and Audit Committee Effect on Audit Delay with Public Accounting Firms' Reputation as Moderator Variables - Fitria Nita Rahajaan; Syamsuri Rahim (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
The purpose of this research is to analyze and examine the effect of profitability, firm size, and the audit committee on audit delay if it is moderated by the reputation of the public accounting firms. This research was conducted at mining companies listed on the Indonesia Stock Exchange in 2016 - 2019. The samples taken in this study were 22 companies with an observation period of 4 years with 88 observations. The research sample was determined using the purposive sampling method. Data collection was carried out using non-participant observation methods. This research's analysis technique is the Structural Equation Model (SEM) based on Partial Least Square (PLS). This study indicates that profitability and the audit committee have a negative and significant effect on audit delay. Firm size has a positive and insignificant effect on audit delay. The reputation of public accounting firms can strengthen the effect of profitability and the audit committee on audit delay. The reputation of public accounting firms is not able to strengthen the influence of firm size on audit delay.